Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; afro-féminisme; amériques; anthologie; approches et analyses; cours; discipline; fem1000; femmes* noires; féminismes noirs; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; afro-féminisme; amériques; antiesclavagisme; approches et analyses; cours; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminismes noirs; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis